Pediatric Percutaneous Nephrolithotomy in a Peripheral Tertiary Care Center in Nepal - Gupta, Dipesh K; Jaiswal, Deepak (Journal of Institute of Medicine Nepal, 2020)
Introduction Pediatric nephrolithiasis though uncommon, poses clinical management dilemma due to anatomical and physiological factors. Percutaneous Nephrolithotomy (PCNL) is well established in adults and miniaturization of the instruments has helped to expand its indication for uses in pediatric population with equivalent results. The aim of our study is to evaluate the application of the procedure in our settings.MethodsThis was a retrospective study done at Nepalgunj Medical College teaching hospital from June 2017 to April 2020. Total of 75 patients with 76 renal units under 18 year of age were evaluated. PCNL was done in prone position in all patients using fluoroscopy for initial puncture and subsequently for clearance. The size of the tract varying from 15 Fr to 24 Fr was decided based on the degree of hydronephrosis.ResultsMean stone volume was 372 mm2. With mean operative time of 58 min, 96% of stone clearance rate was achieved. Mini PCNL was done in most of the cases. Single tract was used in 84% cases mostly with subcostal puncture. Major complications were pelvic perforation in 4% cases and two patients required restaging.ConclusionPCNL in pediatric population is safe with good stone free rate with minimal complications. Application of miniaturized instruments has further improved the outcome with comparable morbidity.